If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3t + 5 = 26 Reorder the terms: 5 + -3t = 26 Solving 5 + -3t = 26 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3t = 26 + -5 Combine like terms: 5 + -5 = 0 0 + -3t = 26 + -5 -3t = 26 + -5 Combine like terms: 26 + -5 = 21 -3t = 21 Divide each side by '-3'. t = -7 Simplifying t = -7
| 4x-2x+3-8=7x-5+4x | | 3t+5=26 | | (x^2+y^4)(x^2-y^4)=0 | | 0.67x+7=21 | | 72+36=0 | | 5x-2+8=7x-4 | | 21=8x-75 | | 6a+5x=36 | | (4s+4)(4s-4)=0 | | 3x+y+z=14 | | (3r-1)(4r-3)=0 | | 15-8m=73 | | -8x+6x-7x=3x(4-3)-5x-15 | | 98p=197 | | 5/3= | | 170-2x=25x+20 | | -5=15+4x | | 5x-x+3=-x+7 | | 5-9x=37-16x | | 3n+4=56 | | 3(4i)+2(7i)= | | 3(2x-3)-2x=8-2(3x+1) | | 5x-8-3x-9=-12x+11 | | y^2+4x-4y-12=0 | | 10n+5=9n | | 23+1z=3 | | 3(t+2)=9(t-2) | | e+2(e+4)+3e=56 | | 99-2x=4-9x | | x^2-9xy-10y^2=0 | | 87-6x=10+23x | | 6x-2(x+5)=4x-1 |